EFEKTIVITAS PENGGUNAAN VIRTUAL LABORATORY TERHADAP PENINGKATAN HASIL BELAJAR SISWA SMA DI ERA NEW NORMAL - Chyntia Clarinda; Novalina; Mariana Gu; Faradiba Faradiba (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Technological developments present many choices of learning media. The learning media that is the prima donna during the pandemic is a virtual laboratory. Virtual laboratories are used by teachers as a substitute for face-to-face practicum activities. There are many kinds of virtual laboratory applications that have been spread, one of which is the